2017
DOI: 10.1097/md.0000000000008300
|View full text |Cite
|
Sign up to set email alerts
|

Dose, duration and strain of bacillus Calmette–Guerin in the treatment of nonmuscle invasive bladder cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 45 publications
(89 reference statements)
2
30
0
1
Order By: Relevance
“…In previous studies, dose and maintenance therapy of intravesical BCG treatment resulted in significant benefits in reducing the recurrence rate after TURBT. However, there were no significant differences in other oncologic outcomes such as PFS, OS and cancer-specific survival (CSS)[15, 18, 19] similar to our study results. BCG maintenance treatment was significantly associated with RFS, although the patients were different.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In previous studies, dose and maintenance therapy of intravesical BCG treatment resulted in significant benefits in reducing the recurrence rate after TURBT. However, there were no significant differences in other oncologic outcomes such as PFS, OS and cancer-specific survival (CSS)[15, 18, 19] similar to our study results. BCG maintenance treatment was significantly associated with RFS, although the patients were different.…”
Section: Discussionsupporting
confidence: 86%
“…In univariate and multivariate analyses of risk factors for RFS, the BCG maintenance therapy (HR 0.278, IQR 0.091–0.849, P = 0.050) was the only significant factor (Table 2). Although repeat TURBT patients were not included in the study, RCTs reported differences in prognosis according to BCG duration[15]. Clinical trials of SWOG reported a significantly better prognosis in the maintenance group compared with the control group only with induction.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, MT was performed with a half dose of the Tokyo strain and was continued in 2-week cycles. Data regarding this regimen are extremely limited, even in the era of a BCG shortage [3,[9][10][11]. We retrospectively investigated the efficacy and safety of MT with LD-BCG for patients following TURBT for intermediate-to-highrisk NMIBC.…”
Section: Discussionmentioning
confidence: 99%
“…IVIT is now a standard treatment [1,[18][19][20] after TUR for T1 tumours but was not established as the primary management in the present early series and such a treatment might have improved our recurrence rate. Intravesical BCG is reported to have an impact on progression by some authors [21] and not to have an impact on progression by others [22,23]. In the present study, IVIT had a strong impact on progression, but in patients with low RV or RTV compared to those with high RV or RTV progression rates were similar with or without BCG, and therefore all patients were included in the analysis irrespective of BCG treatment.…”
Section: The Quality Of the Primary Resectionmentioning
confidence: 44%